The Unknown Guest - Maeterlinck, Maurice, 1862-1949; Teixeira de Mattos, Alexander, 1865-1921 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Unknown Guest" by Maurice Maeterlinck is an analytical essay that delves into the phenomena of supernatural occurrences, written during the late 19th century. This work explores themes surrounding the manifestations of the unknown, such as veridical apparitions, psychic phenomena, and the deeper connections between life and death. The author draws upon extensive research conducted by psychical societies to examine the nature of inexplicable events and their implications for human understanding. The opening of the work establishes Maeterlinck's intention to investigate the current understanding of supernatural experiences. He discusses various classifications of apparitions, including hallucinations from the living and the dead, and introduces concepts like psychometry and telepathy. The chapter outlines key ideas and evidence from scientific inquiry, with a focus on how intense emotions can manifest as psychic phenomena, suggesting that there exists an unexplored realm beyond conventional science. By compiling examples and observations, Maeterlinck sets the stage for a larger discourse on the mysteries that challenge the boundaries of human comprehension. (This is an automatically generated summary.)
Phantasms of the living and the dead -- Psychometry -- The knowledge of the future -- The Elberfeld horses -- The unknown guest.
Release date is 2000-01-01
Scanned by Dianne Bean of Phoenix, Arizona
Keywords: Parapsychology